Tuberculosis pericarditis: a case report - Louis, Martine A.; Singh, Arpana S.; Bhatia, Shubham; Webb, Sheppard C.; Kiarie, Patrick K.; Keating, Luke; Inniss, Kellyann K. (International Surgery Journal, 2024)
Tuberculosis (TB) is still prevalent in the world. In 2020, 1.5 million people died from TB.18 TB accounts for 4% of acute pericarditis. Tuberculous pericarditis (TBP) is due to hypersensitivity to tuberculin protein produced by Mycobacterium tuberculosis and develops in 1-2% of pulmonary TB cases, representing about 1-2% of extrapulmonary tuberculosis. Complications occur in the form of acute pericarditis (4%) and cardiac tamponade (7%), which may require life-saving invasive procedures. Tuberculous pericarditis has an overall mortality rate of 1.43 per 100 person-months over a median follow-up of 11.97 months. Risk factors include diabetes, substance use disorder, HIV-positivity, renal insufficiency, biological or immunosuppressive therapy, and exposure to regions with a high prevalence of tuberculosis. We present a 49-year-old diabetic male with a large complex pericardial effusion occurring three months after a diagnosis of TB pleurisy on antituberculosis drugs, which required pericardiocentesis and pericardial window in the context of cardiac tamponade. Cases of TB pericarditis in developed countries are rarely reported, and there are even fewer in the US. Along with a literature review of the road map for its accurate diagnosis and treatment, this case highlights the relevance of TB in the differential of pericarditis worldwide, even in developed countries.